2007
DOI: 10.1084/jem.20070157
|View full text |Cite
|
Sign up to set email alerts
|

Opposing activities of two novel members of the IL-1 ligand family regulate skin inflammation

Abstract: The interleukin (IL)-1 family members IL-1α, -1β, and -18 are potent inflammatory cytokines whose activities are dependent on heterodimeric receptors of the IL-1R superfamily, and which are regulated by soluble antagonists. Recently, several new IL-1 family members have been identified. To determine the role of one of these family members in the skin, transgenic mice expressing IL1F6 in basal keratinocytes were generated. IL1F6 transgenic mice exhibit skin abnormalities that are dependent on IL-1Rrp2 and IL-1R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
347
0
9

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 318 publications
(374 citation statements)
references
References 37 publications
18
347
0
9
Order By: Relevance
“…We cannot, as yet, say whether maturation of human DC subsets via IL-1Rrp2 and its ligands has an important role in vivo. However, in murine models of psoriasis, over-expression of IL-1F6 in murine basal keratinocytes (in an IL-1F5 −/− background) induces increased skin inflammation and both IL-1F6 and IL-1F5 are increased in human psoriatic skin [28]. Both IL-1F5 and IL-1F6 function via IL-1Rrp2 and this study may indicate that the consequence of IL-1Rrp2 expression and production of IL-1F6 has pro-inflammatory rather than anti-inflammatory effects, and studies which have shown that IL-1F6-, IL-1F8-and IL-1F9-induced nuclear translocation of NF-κB in epithelial cells [3] may also provide circumstantial evidence for this.…”
Section: Discussionmentioning
confidence: 99%
“…We cannot, as yet, say whether maturation of human DC subsets via IL-1Rrp2 and its ligands has an important role in vivo. However, in murine models of psoriasis, over-expression of IL-1F6 in murine basal keratinocytes (in an IL-1F5 −/− background) induces increased skin inflammation and both IL-1F6 and IL-1F5 are increased in human psoriatic skin [28]. Both IL-1F5 and IL-1F6 function via IL-1Rrp2 and this study may indicate that the consequence of IL-1Rrp2 expression and production of IL-1F6 has pro-inflammatory rather than anti-inflammatory effects, and studies which have shown that IL-1F6-, IL-1F8-and IL-1F9-induced nuclear translocation of NF-κB in epithelial cells [3] may also provide circumstantial evidence for this.…”
Section: Discussionmentioning
confidence: 99%
“…There is now mounting evidence, from murine studies, that the IL-36R/IL-36α axis may have an important role in skin disorders [1][2][3]. This could also be the case in humans since missense mutations within IL-36RN genes, which encode for IL-36RA, an IL-36R antagonist, have been shown to be associated with pustular psoriasis [4].…”
Section: Introductionmentioning
confidence: 99%
“…In vitro analysis clarified that Il1f6 mRNA expression in epithelial cells could be induced by stimulation of the immune cells. Blumberg et al 27 reported that transgenic mice overexpressing dermal IL-1F6 showed acanthosis and increase in the number of macrophages and T-cells in these lesions; they also suggested that IL-1F6 controlled tissue injuries, promoting local inflammation. These findings strongly suggested that IL-1F6 in renal tubules was associated with local vicious cycles of tubulointerstitial inflammation.…”
Section: Il-1f6 In Mouse Models Of Renal Diseases O Ichii Et Almentioning
confidence: 99%